1980
DOI: 10.1093/infdis/142.2.250
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Factor in Acute Viral Infections: Interference with Determination of IgM, IgG, and IgA Antibodies in an Enzyme Immunoassay

Abstract: IgM rheumatoid factor (RF), an autoantibody to the Fc fragment of IgG, was determined by solid-phase enzyme immunoassay (EIA). RF levels were significantly higher in patients with rubella virus infection than in patients with infections due to influenza virus, cytomegalovirus, respiratory syncytial virus, parainfluenza virus, adenovirus, mumps virus, or herpes simplex virus. To evaluate the role of RF in EIA determinations of viral antibodies, IgM RF from IgM-IgG cryoglobulin or control IgM was added to patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 16 publications
1
56
0
1
Order By: Relevance
“…These results suggest that IgM responses were seen largely in a Assay sensitivities were based on antibody responses obtained in convalescent-phase sera from A(H1N1)pdm09-infected persons. All had MN antibody titers of Ն40 and HI antibody titers of Ն20 (Veguilla et al [24]). Sera were grouped by age or by primary or nonprimary infections status determined as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that IgM responses were seen largely in a Assay sensitivities were based on antibody responses obtained in convalescent-phase sera from A(H1N1)pdm09-infected persons. All had MN antibody titers of Ն40 and HI antibody titers of Ն20 (Veguilla et al [24]). Sera were grouped by age or by primary or nonprimary infections status determined as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, GullSORB treatment has been employed widely to eliminate the effect of rheumatoid factor, which causes false-positive IgM results (25,26). While IgG depletion eliminated the FRET signal from all the past-infection samples and the false-positive seronegatives, 58/61 (95%) acute-phase sera remained positive (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been published demonstrating interference from RF and heterophile antibodies in immunoassays (8,9,17). Recent studies have shown the importance of including a background subtraction procedure to eliminate falsepositive reactions from interference by these substances when testing for WNV IgM antibodies.…”
Section: Discussionmentioning
confidence: 99%